Strategies Employed by UMKM Carica Gemilang Wonosobo in Facing Digital Competition - Handayani, Klarita; Rahayu, Angelia Santi; Indrayani, Diana; Fitriani, Fella Yunita (UM Purwokerto Press, 2025)
This study analyzes the strategies of UMKM Carica Gemilang in Wonosobo to face digital competition. A quantitative survey reveals that the implementation of digital marketing significantly enhances sales performance and brand awareness for UMKM Carica. Strategies include utilizing social media, e-commerce platforms, and engaging marketing content. The optimization of information and communication technology through social media and Shopee is effective in increasing product visibility. The research recommends that UMKM Carica continue to develop their digital strategies to tackle increasingly fierce competition, thereby fostering sustainable business growth. Thus, adapting to technological changes is key to the success of UMKM in the digital era.